FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN KONSUMEN PRIMER YANG TERDAFTAR DI BEI - Betharia Kurniati; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research is to break down the effect of cash conversion cycle, sales growth, net working capital, profitability, and cash flow on cash holding in consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2019-2021. The sample of this research was selected using a purposive sampling method with a total valid data of 43 companies. This research data was processed using multiple regression analysis by SPSS program (Statistical Product and Service Solution) version 25 and Microsoft Excel 2019. The result of this research shows cash conversion cycle, and net working capital have significant effect on cash holding, and sales growth, profitability, and cash flow have no effect on cash holding. The implication of this research is to provide knowlegde to companies about the importance of the role of cash holdings as company’s operational funds and to be considered by investors by looking at the company’s cash holding ratio for further